Park&Ride Car Parks as an Element of Improving the Quality of the Transport System in Wroclaw - Sokołowski, Jakub (Parkingi park&ride jako element poprawy jakości systemu transportowego we Wrocławiu, 2022)
The traffic problems of modern cities are mainly caused by increased intensity of car traffic. The key to encouraging city users to use public transport services is to increase the level of quality and accessibility. Park&ride car parks (P+R) are one element of a strategy to increase the quality of public transport systems, in this case the public transport system in Wroclaw. The aim of the study was to indicate the importance of park&ride facilities in building and improving the quality of the public transport system in Wroclaw. The study used the desk research method, the descriptive method and the results of document analysis. The research procedure established that the process of constructing park&ride facilities (which are an element of the public transport system in Wroclaw) is being implemented continuously; at the same time it has a positive impact on reducing the level of car traffic. The current implementation period and the availability of P+R car parks in Wroclaw are insufficient in comparison with the needs of such a large urban centre, which is constantly developing.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 105-115
Keywords: car parks; park&ride; quality improvement; accessibility; transport system; Wroclaw; parkingi; podnoszenie jakości; dostępność; system transportowy; Wrocław